Scintillation material on the basis of BaₓSr₁₋ₓI₂:Eu solid solutions - Rebrova, N.V.; Cherginets, N.N.; Ponomarenko, T.V.; Rebrova, T.P.; Vjunnik, I.N.; Zelenskaya, O.V.; Kosinov, N.N. (Functional Materials, 2009)
Single crystals of solid solutions Srl₂:Eu, Bal₂:Eu and BaₓSr₁₋ₓI₂:Eu with concentration of Eul₂ equal to 0.5 mol. % were grown by Bridgman-Stockbarger method. Addition of Bal₂ to Srl₂:Eu is found to cause arising two emission bands in the luminescence spectrum. One of them with maximum ea 430 nm is usual for Eu-containing halides, another with maximum at wavelength in 550-580 nm range is characterized by the shift of maximum position at varying Bal₂ concentration. The latter band arising is explained by distortions of crystal lattice of solid solution as compared with that of Bal₂ or Srl₂ since Sr²⁺ and Eu²⁺ from the one hand and Ba²⁺ from the other one have appreciably different radii. As a result, the light yield for the obtained materials decreases and the energy resolution deteriorates. Методом Бріджмена-Стокбаргера вирощено монокристали Srl₂:Eu, Bal₂:Eu та твердих розчинів BaₓSr₁₋ₓI₂:Eu з концентрацією активатора 0,5 мол. %. Додавання до Srl₂:Eu йодиду барію веде до появи двох піків у спектрі люмінесценції. Перший з них є притаманним для європій-вмісних матеріалів (максимуми поблизу 430 нм), другий з максимумом в області 550-580 нм, при підвищенні концентрації ВаІ₂ положення максимуму зміщується у довгохвильову область. Згаданий пік з'являється як наслідок спотворень кристалічної гратки твердого розчину з огляду на значну відмінність іонних радіусів Sr²⁺ та Eu²⁺, з одного боку і Ва²⁺, з іншого. В наслідок цього зміньшується енергетичне розділення одержаних матеріалів. Методом Бриджмена-Стокбаргера выращены монокристаллы Srl₂:Eu²⁺, Bal₂:Eu и твердых растворов BaₓSr₁₋ₓI₂:Eu с концентрацией активатора 0,5 мол. %. Добавление в Srl₂:Eu йодида бария приводит к появлению двух пиков в спектре люминесценции. Первый из них характерен для европий-содержащих материалов (максимумы вблизи 430 нм), второй с максимумом в области 550-580 нм, по мере повышения концентрации ВаI₂ положение максимума смещается в длинноволновую область. Упомянутый пик появляется как следствие искажений кристаллической решетки твердого раствора из-за значительного различия ионных радиусов Sr²⁺ и Eu²⁺, с одной стороны и Ва²⁺ с другой. Вследствие этого уменьшается световыход и ухудшается энергетическое разрешение полученных материалов.